ANALISIS PENGAMBILAN KEPUTUSAN NASABAH PT. BANK MUAMALAT CABANG MAKASSAR (Tinjauan Perilaku Konsumen) - Yuswari Nur (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2015)
This study aims to (a) to determine the effect of involvement and motivation of the customer decision making PT. Bank Muamalat Makassar Branch ; (b) to determine the effect of knowledge and attitude towards customer decision making PT. Bank Muamalat Makassar Branch ; (c) to determine the influence of personalities, values ​​and lifestyle of the customer decision making PT. Bank Muamalat Makassar Branch; (d) to determine the effect of the decision variables simultaneously all customers PT. Bank Muamalat branch Makassar. This study uses quantitative methods and techniques of data collection through a questionnaire with Likert scale that has passed the test of the validity and reliability of the total sample of 100 respondents. Data were analyzed with multiple linear regression analysis using SPSS 16. The results showed that (a) Motivation and Engagement insignificant positive effect on customer decision -making branch of Bank Muamalat Makassar, (b) Knowledge and Attitudes no significant positive effect on customer decision making branch of Bank Muamalat Makassar, (c) Variable Personality, Values ​​and lifestyle significant positive effect on customer decision making branch of Bank Muamalat Makassar, (d) Motivation and Engagement, Knowledge and attitudes, as well as personality, values ​​and lifestyles affect simultaneously or jointly to the customer decision making PT. Bank Muamalat branch Makassar.